2016
DOI: 10.5130/csr.v22i2.4823
|View full text |Cite
|
Sign up to set email alerts
|

Perception, Imagination and Affect in Human–Robot Relationships

Abstract: As they arrive in our homes, nursing facilities and educational institutions, urgent questions are being asked about the ethics of encouraging people to have feelings towards social robots that have roles as companions, carers and teachers. This article suggests that the quality of these debates is enhanced by examining how people perceive robots and, in particular, how robots’ expressive characteristics stimulate feelings through engaging the embodied imagination. I discuss the perception and expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…For example -people have less resistance before turning off the robot (when it refuses) when it behaves more like a machine than a human [109] or it is also non agreeable and unintelligent [80]. Also the content and intensity of emotions can change in interaction with the robot [110][111][112].…”
Section: Discussionmentioning
confidence: 99%
“…For example -people have less resistance before turning off the robot (when it refuses) when it behaves more like a machine than a human [109] or it is also non agreeable and unintelligent [80]. Also the content and intensity of emotions can change in interaction with the robot [110][111][112].…”
Section: Discussionmentioning
confidence: 99%
“…As we noted above, Haraway's (2003) view of animals, especially pets, as companion species has been suggested to cover social robots as well (Kerruish 2016;Šabanović 2020). Throughout her work, Haraway has highlighted how nonhuman living beings and nonliving entities shape humans and, in particular, reshape our notions of subjectivity and gender.…”
Section: Boundaries Between Nonliving Things and Living Beingsmentioning
confidence: 99%
“…Recent theoretical and empirical studies on social companion robots have suggested that these machines fall into the category of companion species (Kerruish 2016;Šabanović 2020), a concept that has been reinvigorated from Donna Haraway's (2003) categorization of animals as companion species. Kerruish (2016) proposes that social robots, as artificial pets, could be categorized as companion species on the grounds that interactions between the human and the robotic animal consist of bonding and co-shaping, similarly to human-pet interactions. In 2020, Šabanović supported the view by presenting the idea of domesticated robots as pet-like "creatures of possibilities"-which are defined by Agamben (1999) as entities with a repertoire of bodily actions and experiences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technical emphasis in this “new” paradigm appears to be on automation technologies, for example robots encompassing cognitive functions (e.g. natural language processing), artificial intelligence and machine learning and algorithms mimicking management functions (Wang et al , 2017) and even social and emotional labour (Breazeal, 2002; Kerruish, 2016). However, some aspects emphasize communication and digital connectivity between humans, technology, and nature through big data, wearable devices, “smart cities,” and “smart factories,” and “the Internet of things”, and human augmentation through nano- and bio-technology (Zanella et al , 2014).…”
Section: Introductionmentioning
confidence: 99%